PETROLEUM POTENTIAL OF PRECAMBRIAN AND PALEOZOIC DEPOSITS OF THE SOUTH URALS - Камалетдинов М.А.; Казанцева Т.Т.; Казанцев Ю.В.; Постников Д.В. (My University, 2001)
The history of investigation into the petroleum potential of deep-seated horizons of the Uralian region is reviewed. Two major objects for oil and gas prospecting are considered: 1) Late Precambrian (Riphean and Vendian) deposits in the platform part of the Bashkir Autonomic Republic and 2) Paleozoic and Precambrian underthrust series in the fold-nappe zone of the Urals. The petroleum potential is justified by numerous oil shows on the territory of Bashkiria and in adjacent areas and by the world data on the presence of abundant underthrust petroleum deposits in many countries.
Keywords: Paleozoic; Precambrian; Paleozoic; Докембрий; Precambrian; Палеозой